Effects of a geriatric intervention aiming to improve quality care in nursing homes on benzodiazepine use and discontinuation. (8th January 2016) - de Souto Barreto, Philipe; Lapeyre‐Mestre, Maryse; Cestac, Philippe; Vellas, Bruno; Rolland, Yves
Abstract : Background: Benzodiazepines and "Z drugs" are often prescribed in residents of nursing homes (NH) despite their well‐known deleterious effects. We aimed to investigate if a general intervention on quality of care led to discontinuation of benzodiazepine, and to examine which NH‐related factors were associated in change of benzodiazepines use. Methods: IQUARE is a quasi‐experimental study, investigating the impact of an intervention based on a geriatric education with NH staff on several quality indicators of care (including appropriate prescriptions). All participating NH received an initial and 18‐month audit regarding drug prescriptions and other quality of care variables. The analysis included 3973 residents, 2151 subjects (mean age: 84.6 ± 8.5 years; 74.3% women) in the control group and 1822 (mean age: 85.5 ± 8.1 years; 77.4% women) in the intervention group. Outcomes at 18 months were benzodiazepines use, long‐acting benzodiazepines use, new‐use of benzodiazepines, and discontinuation. The effect of the intervention was investigated using mixed‐effect logistic regression models, including NH variables and residents' health status as confounders. Results: Higher reductions in benzodiazepine use (−2.8% vs. −1.5%) and long‐acting benzodiazepine (−3.7% vs. −3.5%) were observed in intervention group, but not statistically significant. None of the structural and organisational NH‐related variables predicted either discontinuation or new‐use of benzodiazepines; hospitalisations and initial use of meprobamate increased the likelihood of becoming a new‐user of benzodiazepines. Multivariate analysis suggested that living in a particular NH could affect benzodiazepines discontinuation. Conclusions: A general intervention designed to improve overall NH quality indicators did not succeed in reducing benzodiazepines use. External factors interfered with the intervention. Further studies are needed to examine which NH‐related aspects could impact benzodiazepines discontinuation.